SIRT1 Mediates Effects of FGF21 to Ameliorate Cisplatin-Induced Acute Kidney Injury - Chen, Qiongzhen; Ma, Junfeng; Yang, Xiaoning; Li, Qinyao; Lin, Zhuofeng; Gong, Fanghua (Frontiers in Pharmacology, 2020)
Acute kidney injury (AKI) is a common complication in cancer patients. Kidney function is closely related to patients’ quality of life and tumor prognosis. Cisplatin is a highly effective anti-tumor drug. However, the use of cisplatin is limited by its nephrotoxicity. It has been reported that FGF21 has a renal-protective function, but the mechanisms by which it does so remain unclear. In this study, we show that the expression of FGF21 is significantly upregulated in both in vitro and in vivo cisplatin-induced AKI models. Administration of recombinant FGF21 to cisplatin-induced AKI mice resulted in significantly decreased blood urea nitrogen and serum creatinine levels, as well as significantly reduced protein levels of kidney injury molecule-1 (TIM-1), C-caspase 3, and Bax. H&E-stained kidney sections from cisplatin-induced AKI mice treated with recombinant FGF21 showed a relatively normal renal tissue structure, a reduced number of necrotic sites and vacuolar changes, and decreased casts, suggesting alleviated renal tubular injury. Experiments with an AKI cell model (cisplatin-treated HK-2 cells) yielded similar results as the mouse model; recombinant FGF21 significantly downregulated protein expression levels of TIM-1, C-caspase 3, and Bax. Furthermore, administration of recombinant FGF21 to cisplatin-treated AKI models significantly increased SIRT1 expression, and the beneficial effects of FGF21 on kidney injury were reversed by SIRT1 knockdown. Collectively, our results suggest that SIRT1 mediates the protective effect of FGF21 on cisplatin-induced kidney injury.